Fusarium oxysporum f. sp. cubense (E.F.SMITH) Snyder & Hanses e sua disseminação na Serra de Uruburetama, Estado do Ceará, Brasil Fusarium oxysporum f. sp. cubense (E.F.SMITH) Snyder & Hanses and its dissemination at Uruburetama Mountain, State of Ceará (Revista Ciência Agronômica, 2023)
RCA